Pengaruh Kinerja Karbon dan Climate Governance Terhadap Pengungkapan Emisi Karbon dengan Assurance Sebagai Variabel Moderasi - Dewinda Nurshabrina Maulidya; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted to examine the effect of Carbon Performance dan Climate Governance on Carbon Emission Disclosure with Assurance as a moderation. This study uses secondary data collected from the Indonesia Stock Exchange (IDX) and the official websites of each company. This study is a quantitative study and uses multiple linear regression analysis with the research population being energy sector companies in 2021-2023 with a total sample of 100 data. The results of the hypothesis testing in this study indicate that Carbon Performance and Climate Governance have a positive effect on Carbon Emission Disclosure. Meanwhile Assurance has no effect on Carbon Emission Disclosure. In addition, Assurance is unable to moderate between Carbon Performance and Climate Governance with Carbon Emission Disclosure. By using this research, companies can improve carbon emission disclosure by improving carbon performance and by implementing Climate Governance.